Peran Financial Knowledge Dan Financial Attitude Terhadap Financial Management Behavior - Farichatul Izzah; Feri Dwi Riyanto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The purpose of this research is to know the role  financial knowledge  and  financial attitude  against  financial management behavior .  People's well-being can be experienced if the financial management system can be lived as well as possible.   In reaching  Financial Management Behavior   needed Financial  Knowledge  and  Financial  Attitude  the positive and the right one to apply directly. Without applying  Financial  Knowledge  and  Financial  Attitude  the good one , then  it's hard for individuals to guarantee their lives in the term  Long.  This research is a type of empirical research by using qualitative descriptives that are trying to define, write, analyze and express what is observed   with   use   method   analysis   concept/isi   (text).   Research  the one   done   is researching every text contained in several journals  and book.  The data source in this writing is primary data in the form of related journals   and   secondary data in the form of books.   Data   the one   had been   collected   next   analyzed   with   use content analysis methods ( Content Analysis ) .  The conclusion of this study is a danya  Financial Knowledge  then being able to master, analyze and manage financially to make something financial determination so that it has good behavior management.  Financial  attitude  have a role   against  Behavior management   i.e. d engan has insight to manage financially, but just a little financial insight is possessed so that it causes people to be less suitable in managing their finances.  Financial Attitude   will  influence on  Financial Management Behavior   cause   is one of the facades that influences financial attitudes accompanied by good financial management behavior.